2018
DOI: 10.1097/01.naj.0000532806.35972.29
|View full text |Cite
|
Sign up to set email alerts
|

CE: Original Research: Exploring Clinicians’ Perceptions About Sustaining an Evidence-Based Fall Prevention Program

Abstract: Individual professional perceptions and practices, as well as organizational characteristics, affect the sustainability of evidence-based fall prevention practices. While all team members recognized patient falls as a significant quality and safety issue, most believed that direct care nurses hold primary responsibility for leading fall prevention efforts. The data support the importance of effective interprofessional team communication and organizational practices in sustaining an evidence-based fall preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Child et al [4] have emphasized that it is necessary to address attitudes, beliefs, and behaviors at the individual, organizational, and societal levels in order to improve the implementation of evidence-based fall prevention programs [4]. Past studies have also explored the perspectives of healthcare professionals and community service providers on EBP [43, 44]. Their findings suggest that, when compared to earlier times, present-day physiotherapists are more likely to view evidence-based practice as an integrated patient-oriented enterprise [43].…”
Section: Introductionmentioning
confidence: 99%
“…Child et al [4] have emphasized that it is necessary to address attitudes, beliefs, and behaviors at the individual, organizational, and societal levels in order to improve the implementation of evidence-based fall prevention programs [4]. Past studies have also explored the perspectives of healthcare professionals and community service providers on EBP [43, 44]. Their findings suggest that, when compared to earlier times, present-day physiotherapists are more likely to view evidence-based practice as an integrated patient-oriented enterprise [43].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses within these studies described the following interventions as being effective in preventing falls for hospitalized adults: assistive mobilization (presence of personnel such as nurses and family members and assistive devices such as walkers and gait belts),10 assessment of fall risk on admission,9,10,20 limitation of risky ambulation,10 and education of patients on medication side effects that could contribute to falls, such as dizziness 10. Nurses within all 5 studies described bed brakes, bed alarms, and/or side rails as effective in the prevention of falls 9,10,16,17,20. Bok et al16 found that after a fall event nurses changed their practice by increasing fall prevention interventions such as use of chair alarms, hourly intentional rounds, and frequent checks on the patients.…”
Section: Resultsmentioning
confidence: 99%
“…10 Nurses within all 5 studies described bed brakes, bed alarms, and/or side rails as effective in the prevention of falls. 9,10,16,17,20 Bok et al 16 found that after a fall event nurses changed their practice by increasing fall prevention interventions such as use of chair alarms, hourly intentional rounds, and frequent checks on the patients. Baris and Intepeler 10 found that nurses suggested that the use of the Foley catheter in patients who have frequent urination/get up to use the bathroom often is helpful in preventing risky ambulation.…”
Section: Nursing Interventions For Fall Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health professionals often face challenges when implementing interprofessional education, such as having separate professional cultures [ 67 ], logistical barriers [ 68 ], limited shared resources in training [ 69 ], and varying clinical practice demands [ 70 ]. By ensuring consistency of patient education content across professions through interprofessional collaborative practice and interprofessional education, the message of falls prevention can be reinforced [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%